Childhood unpredictability and sleep quality in adulthood: the mediating roles of life history strategy and perceived stress - Qi, Wei; He, Xiangyang; Wang, Zhechen (Frontiers in Psychology, 2024)
Background: Early environmental risk have been found to be related to lifelong health. However, the impact of childhood unpredictability, a type of early environmental risk, on health, especially on sleep quality in adulthood, has not been adequately studied. The present study aimed to examine the relationship between childhood unpredictability and sleep quality in adulthood and to explore the possible mediating roles of life history strategy and perceived stress. Methods: A cross-sectional study was conducted on 472 participants from a university in Zhejiang Province, China.The questionnaire inquired about demography, childhood unpredictability, life history strategy (Mini-K), perceived stress (14-item Perceived Stress Scale), and Sleep Quality (Pittsburgh Global Sleep Quality Index). Results: Higher childhood unpredictability was significantly associated with worse sleep quality in adulthood. Moreover, the link between higher childhood unpredictability and worse sleep quality in adulthood was explained by the chain mediation of life history strategy and perceived stress.In line with the life history theory, individuals who have experienced higher unpredictability in childhood tend to develop a faster life history strategy and become more sensitive to stress in adulthood, and subsequently suffer a decrease in sleep quality.